Ethical Challenges Posed by Advanced Veterinary Care in Companion Animal Veterinary Practice - Anne Quain; Michael P. Ward; Siobhan Mullan (Animals, 2021)
Advanced veterinary care (AVC) of companion animals may yield improved clinical outcomes, improved animal welfare, improved satisfaction of veterinary clients, improved satisfaction of veterinary team members, and increased practice profitability. However, it also raises ethical challenges. Yet, what counts as AVC is difficult to pinpoint due to continuing advancements. We discuss some of the challenges in defining advanced veterinary care (AVC), particularly in relation to a standard of care (SOC). We then review key ethical challenges associated with AVC that have been identified in the veterinary ethics literature, including poor quality of life, dysthanasia and caregiver burden, financial cost and accessibility of veterinary care, conflicts of interest, and the absence of ethical review for some patients undergoing AVC. We suggest some strategies to address these concerns, including prospective ethical review utilising ethical frameworks and decision-making tools, the setting of humane end points, the role of regulatory bodies in limiting acceptable procedures, and the normalisation of quality-of-life scoring. We also suggest a role for retrospective ethical review in the form of ethics rounds and clinical auditing. Our discussion reenforces the need for a spectrum of veterinary care for companion animals.